Chọn lựa một hướng đi trong nghiên cứu tổng hợp Oseltamivir (Tamiflu(R)) ở Việt Nam - Chiến, Nguyễn Quyết (Vietnam Journal of Chemistry, 2014)
In view of the avian flu pandemic threat, contemporary achievements on synthesis and production of the neuraminidase inhibitor and anti-influenza drug oseltamivir (Tamiflu(R)) were reviewed and discussed in order to find a feasible approach for Vietnam in the case of emergency